Applied mathematical optimization technique on menu scheduling for boarding school student using delete-reshuffle-reoptimize algorithm - Sufahani, Suliadi; Mahathir Mohamad, Mahathir Mohamad; Roslan, Rozaini; Kamardan, M. Ghazali; Che-Him, Norziha; Ali, Maselan; Khalid, Kamal; Nazri, E.M.; Ahmad, Asmala (2017)
Boarding school student needs to eat well balanced nutritious food which includes proper calories, vitality and supplements for legitimate development, keeping in mind the end goal is to repair and support the body tissues and averting undesired ailments and disease. Serving healthier menu is a noteworthy stride towards accomplishing that goal. Be that as it may, arranging a nutritious and adjusted menu physically is confounded, wasteful and tedious. This study intends to build up a scientific mathematical model for eating routine arranging that improves and meets the vital supplement consumption for boarding school student aged 13-18 and in addition saving the financial plan. It likewise gives the adaptability for the cook to change any favoured menu even after the ideal arrangement has been produced. A recalculation procedure will be performed in view of the ideal arrangement. The information was gathered from the the Ministry of Education and boarding schools' authorities. Menu arranging is a notable enhancement issue and part of well-established optimization problem. The model was fathomed by utilizing Binary Programming and "Delete-Reshuffle-Reoptimize Algortihm (DDRA)".